Exploring Adaptivity in Service Development: The Case of Mobile Platforms. Issue 3 (8th October 2013) - Basoglu, Nuri; Daim, Tugrul; Polat, Ebru
<x xml:space="preserve">Abstract</x> Together with the developing technologies of a fast‐evolving Web environment, computers, and handheld devices, human–computer interaction is gaining more importance. User interface, as the interactive layer between user and information systems, has a great role in system adoption. Based on a technology acceptance model, acceptance of a system can be explained as a function of perceived usefulness (PU) and perceived ease of use (PEOU). Because several external variables have impact on PU and PEOU, the content and interface design of every single application should be addressed accordingly in a way that enhances the consumer's attitude about using the system by considering the impact of external variables through system usage. The objective of this study was to uncover potential external variables that may influence PEOU and PU, and indirectly influence behavioral attitude in mobile service acceptance and to explore the effects of those variables, primarily adaptivity and the relationships of all the variables among each other, through the limited interface of a mobile platform. Thus, developers will be able to relate the tuning of product features to the adoption of the products they are developing based on a platform.